A note on the existence of Psi-bounded solutions for a system of differential equations on R - Aurel Diamandescu (Electronic Journal of Differential Equations, 2008)
We prove a necessary and sufficient condition for the existence of Psi-bounded solutions of a linear nonhomogeneous system of ordinary differential equations on R.